2019
DOI: 10.1002/sce.21511
|View full text |Cite
|
Sign up to set email alerts
|

Opening up curricula to redistribute epistemic agency: A framework for supporting science teaching

Abstract: This study proposes a strategic framework to guide teachers' curriculum adaptation, planning, and enactment as a lever for redistributing epistemic agency. This framework intends to position teachers as strategic decision-makers around when and how to open up aspects of their curriculum. We argue that seeing the aspects of Next Generation Science Standardsaligned curricula-the methods of investigation, the anchoring phenomena, and the explanatory models students construct-as entry points for redistributing epi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
73
1
10

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(99 citation statements)
references
References 105 publications
7
73
1
10
Order By: Relevance
“…Classrooms that center on the pursuit of students’ own ideas also provide opportunities for authentic engagement in disciplinary practices and sense‐making (Ball, 1993; Colley & Windschitl, 2016; Engle & Conant, 2002; Hammer, 1997; Schwarz, Passmore, & Reiser, 2017). Some authors highlight that this kind of pursuit recognizes students’ agency in the construction of ideas (Duckworth, 2001; Ko & Krist, 2019; Sikorski, 2016). Finally, responsive instruction—and particularly its framing of students’ ideas as generative beginnings for their learning—shifts away from a “dichotomous view” (Warren, Ballenger, Ogonowski, Rosebery, & Hudicourt‐Barnes, 2001, p. 531) of student thinking, which focuses on the compatibility (or incompatibility) of students’ everyday ways of knowing and those of scientists.…”
Section: Rt In the Literaturementioning
confidence: 99%
“…Classrooms that center on the pursuit of students’ own ideas also provide opportunities for authentic engagement in disciplinary practices and sense‐making (Ball, 1993; Colley & Windschitl, 2016; Engle & Conant, 2002; Hammer, 1997; Schwarz, Passmore, & Reiser, 2017). Some authors highlight that this kind of pursuit recognizes students’ agency in the construction of ideas (Duckworth, 2001; Ko & Krist, 2019; Sikorski, 2016). Finally, responsive instruction—and particularly its framing of students’ ideas as generative beginnings for their learning—shifts away from a “dichotomous view” (Warren, Ballenger, Ogonowski, Rosebery, & Hudicourt‐Barnes, 2001, p. 531) of student thinking, which focuses on the compatibility (or incompatibility) of students’ everyday ways of knowing and those of scientists.…”
Section: Rt In the Literaturementioning
confidence: 99%
“…Sendo mobilizados para o Levou à construção de et al, 2019). Concordamos com autores que têm indicado a necessidade de posicionar os estudantes como agentes epistêmicos, ao invés de simplesmente demonstrarem uma aprendizagem declarativa de processos científicos ou a reprodução de habilidades relacionadas ao chamado "método científico" (Kelly & Licona, 2018, Ko & Krist, 2019, Stroupe et al, 2019.…”
Section: Engajamento Em Práticas Do Par [Epistêmico+social]unclassified
“…Por um lado, pesquisadores têm indicado que explicar como funcionam os processos da ciência, ensinando cada passo da metodologia científica ou desenvolvendo atividades experimentais para que os alunos confirmem o conhecimento conceitual não significa, necessariamente, introduzi-los no legado epistêmico da ciência (Stroupe, 2015;Manz, Lehrer & Schauble, 2020;Ko & Krist, 2019). Seria necessário gerar oportunidades para que estudantes vivenciassem a construção do conhecimento, se apropriando daquilo que estão fazendo a partir de critérios utilizados pela ciência e tomando decisões coletivamente (Carvalho, 2018;Ko & Krist, 2019).…”
Section: Introductionunclassified
“…On the one hand, researchers have shown that explanation of how scientific processes work, teaching each step of scientific methodology or developing experimental activities so that the students may confirm conceptual knowledge, does not necessarily mean their introduction into the epistemic legacy of science (Stroupe, 2015;Manz et al, 2020;Ko & Krist, 2019). It would be necessary to create new opportunities so that the students could experience the construction of knowledge, appropriating whatever they are doing based on criteria used by science and collectively taking decisions (Carvalho, 2018;Ko & Krist, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In spite of these recommendations, as Ko and Krist (2019) emphasize, Science curricula are still largely based on a central axis of well-defined conceptual goals. With the teacher's work carried out around this axis, there is still a lingering tension with regard to how the concepts are taught.…”
Section: Introductionmentioning
confidence: 99%